The role of tax instruments in stimulation of innovation development. - Ozhaubayeva, A. T. (Journal of Economic Research & Business Administration, 2015)
The article is devoted to instruments for forming innovation economics and development of innovation process as the main and actual trend in this time. The stimulation instruments are divided into direct and indirect types and they are used accordingly. By the author concludes by emphasizing the fact that rates of economic innovation of Kazakhstan are developing very slowly.